Ethical, Translational, and Legal Issues Surrounding the Novel Adoption of Ectogestative Technologies - Segers S; Romanis EC (Dove Medical Press, 2022)
Seppe Segers,1 Elizabeth Chloe Romanis2,3 1Department of Health, Ethics, and Society, Research Institutes GROW and CAPHRI, Maastricht University, Maastricht, the Netherlands; 2Edmond & Lily Safra Center for Ethics and Petrie-Flom Center for Health Law Policy, Biotechnology and Bioethics, Harvard University, Cambridge, MA, USA; 3Centre for Law and Ethics in the Life Sciences, Durham University, Durham, UKCorrespondence: Seppe Segers, Email seppe.segers@maastrichtuniversity.nl; seppe.segers@ugent.beAbstract: Increasing numbers of research teams are investigating the feasibility of developing artificial amnion and placenta technology (AAPT), commonly referred to as "artificial womb technology". This technology, aimed at supporting ex vivo gestation, has not yet been tested in humans, but it has been stated that we are closer to clinical application than ever before as breakthroughs in animal studies demonstrate good proof of principle. With these proof-of-concept models, further dissemination of AAPT as a research modality is expected. In this review article, we consider the ethical implications of the most imminent anticipated applications for AAPT. We focus specifically on the specific ethical complications regarding the improvements this technology may offer to conventional neonatal intensive care, its potential utility in facilitating prenatal interventions, and some of the broader socio-legal implications such as the debates about abortion access and reproductive and gestational choices. We discuss translational and societal questions when it comes to designing and developing this technology, like commitments to value-sensitive design, along with an examination of the legal and moral status of the entity gestating ex utero, which will be relevant for how it ought to be treated in the context of these various applications. From these perspectives, this review identifies the ethical questions that we believe to be most pressing in the development and potential introduction of AAPT, with due attention to their manifestation as translational and legal issues.Keywords: ectogestation, artificial amnion and placenta technology, artificial womb technology, obstetrics, neonatology, abortion